The Development Of On-Board Communication System For A Cubesat - Fadzil, Sharfa Eliya Mohd (Universiti Sains Malaysia, 2021)
People sent satellite to the outer space with their own unique missions which gives benefits in return. Now a IU CubeSat has been chosen widely due to its size, compatibility, and very low in cost compared to other traditional satellites. There are many subsystems that contribute to the development of a CubeSat which are power system, payload, thermal, computer system, structure, on board data handling and communication. On board communication system is very crucial in making sure that the CubeSat can operates well. In order for the satellite to achieve its mission, the communication system is important for sending the command from ground station to the satellite and sending the data to the ground station. Since the mission of MYSat is to measure the electron-density in ionosphere E-layer, the data need to be collected to the ground station for further analysis. No communication system means no transmission data will happened and the mission will be unachievable. Command and data handling system also work together with the communication system, as the data will be transmitted to the ground station. The developing process of this CubeSat called MYSat includes in determining the design parameters, conduct experiments involving basic of Morse code for CubeSat, and test and propose RF Transmitter and Receiver 433MHz for on-board communication system for CubeSat. From the findings, the RF Transmitter and Receiver 433MHZ can be used for CubeSat since it operates at real frequency for amateur radio.